Little Hankel Operators on the Weighted Bergman Space of the Unit Ball (Communications in Mathematical Research, 2021)
In this paper we mainly consider little Hankel operators with square-integrable symbols on the weighted Bergman spaces of the unit ball. We obtain thatSchatten class of little Hankel operators is equivalent to Schatten class of positiveToeplitz operators under the conditions that $SMO(f) ∈ L^{\frac{p}{2}}(B_n, dλ)$ and $2 ≤ p